2013
DOI: 10.1111/btp.12057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Terrestrial Molluscs on Litter Decomposition and Nutrient Release in a Hawaiian Rain Forest

Abstract: The roles of terrestrial molluscs in many important ecosystem processes are largely unknown, particularly in tropical forests. It has been suggested from studies in temperate forests that snails/slugs contribute to litter decomposition directly (by their own metabolism) and/or indirectly (by habitat modification enhancing micro‐arthropod or microbial activity). Forty‐two mesocosms were established at seven Hawaiian rain forest sites to examine the role of the five most abundant snail/slug species: the native S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
(53 reference statements)
0
15
0
1
Order By: Relevance
“…From the data presented it may be clear that the ecology of nearly all species listed in this paper is still hardly known or very poorly understood. Meyer III et al (2013) have shown that terrestrial gastropods can play a major role in litter decomposition in tropical habitats and the presence of gastropods increased litter decomposition rates; the highest decomposition rates were those with the greatest gastropod biomass. Furthermore, although there were differences in the rates of release of some nutrients among treatments, the different gastropod species appeared to influence nutrient release in a similar way.…”
Section: Discussionmentioning
confidence: 99%
“…From the data presented it may be clear that the ecology of nearly all species listed in this paper is still hardly known or very poorly understood. Meyer III et al (2013) have shown that terrestrial gastropods can play a major role in litter decomposition in tropical habitats and the presence of gastropods increased litter decomposition rates; the highest decomposition rates were those with the greatest gastropod biomass. Furthermore, although there were differences in the rates of release of some nutrients among treatments, the different gastropod species appeared to influence nutrient release in a similar way.…”
Section: Discussionmentioning
confidence: 99%
“…Litterbags (20 cm × 12.5 cm) were prepared with polyethylene screen of 1 mm mesh size in order to minimise loss of litter fragments [55]. On each litter bag, eight larger round openings (d = 5 mm) were made, with a punch, on both faces of the litterbags to facilitate access of micro-and macro-arthropods, soil molluscs (snails and slugs) and juvenile Lumbricus species [53,56,57]. Litterbags were filled with a precisely weighed quantity of air-dried litter (approximately 3 g, or 8 to 15 leaves, depending on the poplar clone).…”
Section: Leaf Litter Sampling and Decomposition Studymentioning
confidence: 99%
“…Leaf litter is a key habitat and food resource for these ground‐dwelling detritivores, which play a key functional role in nutrient cycling through litter consumption and promotion of microbial growth (Meyer et al. ). Bultman and Uetz () demonstrated through leaf litter manipulation experiments that litter depth increased structural complexity that was important for supporting high abundances of litter‐dwelling spiders.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that snails are promoted by increased leaf litter was not surprising as higher snail abundance is commonly found in higher amounts of litter (Aubry et al 2005, Liew et al 2010, de Chavez and de Lara 2011, including on Christmas Island . Leaf litter is a key habitat and food resource for these ground-dwelling detritivores, which play a key functional role in nutrient cycling through litter consumption and promotion of microbial growth (Meyer et al 2013). Bultman and Uetz (1982) demonstrated through leaf litter manipulation experiments that litter depth increased structural complexity that was important for supporting high abundances of litter-dwelling spiders.…”
Section: Increased Habitat and Resourcesmentioning
confidence: 99%